2014
DOI: 10.1002/cplu.201402078
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Henry and Aza‐Henry Reaction in the Synthesis of (R)‐Tembamide Using Efficient, Recyclable Polymeric CuII Complexes as Catalyst

Abstract: Chiral copper(II) polymeric [H4]salen (salen=bis[(salicylidene)ethylenediaminato]) complexes CuII‐1–3 were generated in situ and used as efficient catalysts in the asymmetric Henry and aza‐Henry reaction of various aromatic and aliphatic aldehydes and N‐tosylimines in the presence of various nitroalkanes at room temperature (27±2 °C) for 20 hours. This group of polymeric [H4]salen complexes demonstrated excellent performance (product yield and enantiomeric excess ee up to 98 %) in the formation of β‐nitroalcoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…The second step involves the coordination of CuI to the imino nitrogen, thus activating the imine by formation of a positively charged nitrogen atom, making it a stronger electrophile. This type of activation is typical of copper catalysts used in the nitro-Mannich reaction [52]. Moreover, validity of the possible mechanism was shown by the fast reaction times and high yields obtained with electron-donating groups since these resulted in a greater electron density on the C=N, which helped the activation of the imine by coordinating with the Lewis acid Cu + catalyst.…”
Section: Figure 10 Mechanistic Aspectsmentioning
confidence: 74%
See 1 more Smart Citation
“…The second step involves the coordination of CuI to the imino nitrogen, thus activating the imine by formation of a positively charged nitrogen atom, making it a stronger electrophile. This type of activation is typical of copper catalysts used in the nitro-Mannich reaction [52]. Moreover, validity of the possible mechanism was shown by the fast reaction times and high yields obtained with electron-donating groups since these resulted in a greater electron density on the C=N, which helped the activation of the imine by coordinating with the Lewis acid Cu + catalyst.…”
Section: Figure 10 Mechanistic Aspectsmentioning
confidence: 74%
“…Moreover, validity of the possible mechanism was shown by the fast reaction times and high yields obtained with electron-donating groups since these resulted in a greater electron density on the C=N, which helped the activation of the imine by coordinating with the Lewis acid Cu + catalyst. It was suggested that the CuI salt coordinates also to the nitroalkane oxygen, increasing its acidity and thus favouring deprotonation to form the reactive nitronate anion [52].…”
Section: Figure 10 Mechanistic Aspectsmentioning
confidence: 99%
“…The polymer was recovered and reused ten times without showing any sign of reduced performance. In the same context, the authors prepared a polymer containing enantiopure copper[H 4 ]salen units, linked together with triazine‐piperazine acting also as basic units . After polymerization and reduction of the salen groups, formation of Cu‐salan derivatives was performed in‐situ for their use as catalysts in the Henry and aza‐Henry reactions.…”
Section: Polymerization Of Salen Derivativesmentioning
confidence: 99%
“…In the same context, the authors prepared a polymer containing enantiopure copper[H 4 ]salen units, linked together with triazinepiperazine acting also as basic units. [53] After polymerization and reduction of the salen groups, formation of Cu-salan derivatives was performed in-situ for their use as catalysts in the Henry and aza-Henry reactions. The presence of the basic moieties of the spacer supported deprotonation of nitromethane to generate the active nucleophile, thus providing good results with a very low catalyst loading.…”
Section: Polymerization Of Salen Derivativesmentioning
confidence: 99%
“…Extracts of Aegle marmelos, containing tembamide, have been used in the Indian traditional medicine as a control for hypoglycemia [43]. Most of the enantioselective procedures to (R)-tembamide involve the use of the corresponding amino alcohol (R)-2e as a key building block [44].…”
Section: Scheme 3 Active Pharmaceutical Ingredients Prepared Startinmentioning
confidence: 99%